THE IMPLEMANTATION OF JIGSAW TECHNIQUE ON STUDENTS’ READING COMPREHENSION IN THE ELEVENTH GRADE OF SMAN 3 BUKITTINGGI - Fadiah Lestari; Absharini Kardena; Loli Safitri; Elsi Amiza (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This research was motivated by the discovery of students who were less enthusiastic about reading and had difficulty understanding the text due to the lack of vocabulary they possessed. Students faced challenges in finding important information in the text. Therefore, the teacher used the jigsaw technique to facilitate knowledge sharing among peers. This study aimed to determine the implementation and constraints of the jigsaw technique. This research design was qualitative and conducted at SMAN 3 Bukittinggi. The informants in this study included an English teacher and two classes of eleventh-grade students. Data were collected through interviews and observations, which were then analyzed by gathering data, reducing data, and drawing conclusions. Based on the results of the research conducted, it was found that Teacher implemented 9 indicators, namely; (1) Divide the students into jigsaw groups of 5 or 6 participants. (2) Appoint one student as the leader for each group (3) Divide the day's lesson into five until six segments. (4) Each student is assigned to learn one chapter. (5) Give students time to read and familiarize themselves with their section, at least twice. (6) Shape temporary